A discourse on religious pluralism: a short survey - Muhamad Shukri, Abdul Salam; Abdul Razak, Mohd Abbas (Department of Usuluddin and Comparative Religion, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University of Malaysia, 2018)
This paper aims to make a short survey on the discourse of religious pluralism nowadays. The emphasis is made on its inception and development, and the personalities who responsible to disseminate this ideology to the Western and Muslim people all over the world. The research employs the qualitative methodology in which the data collected are analyzed using the textual and content analysis approach. Finding reveals that the liberal among the Muslim scholars embrace the interpretation given by John Hick without complaining, while mainstream scholars oppose to it by saying that the true message of the Qur’an is Tawḥīd (Oneness of God) and religious tolerance.